PENGARUH DESAIN PRODUK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN (Survei pada Konsumen UMKM Syehriel Collection) - Ady Nurwana; Ari Arisman; Kusuma Agdhi Rahwana (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2022)
This study aims to determine the effect of Product Design and Product Quality on Purchasing Decisions at the UMKM Syehriel Collection (a survey on the consumers of the UMKM Syehriel Collection). The method used in this research is the quantitative research methods, with a research sample of 100 respondents and the analytical tool used in this study is multiple regression using SPSS version 25. The result showed that the Procut Design and Product Quality a significant effect simultaneously on Purchasing Decisions at the UMKM Syehriel Collection. Product Design has a partially significant affect on Purchasing Decisions at the UMKM Syehriel Collection. Product Quality has a partially not significant effect on Purchasing Decisions at the UMKM Syehriel Collection.